Comparison of the Contributions of CAPLUS and MEDLINE to the Performance of SciFinder in Retrieving the Drug Literature. - Svetla Baykoucheva (Issues in Science and Technology Librarianship)
SciFinder (SF) is a platform that provides access to two large databases, the Chemical Abstracts database (CAPLUS) and MEDLINE. This article analyzes and compares the individual and combined contributions of these two databases to the performance of SF in retrieving the drug literature. Test searches in which the names of two individual drugs (lisinopril and lovastatin) and a group of drugs (SSRI antidepressants) were used as keywords retrieved document sets that were analyzed for total and annual literature output, document types, journal coverage, and language of publication. While the total literature output from CAPLUS was larger than the output from MEDLINE (which was attributed to the presence of patents), MEDLINE performed significantly better than CAPLUS in retrieving the non-patent literature. The overlap of documents between CAPLUS and MEDLINE was found to be only 20-24%, depending on the name of the drug used to perform the searches. This article analyzes the strengths and the weaknesses of CAPLUS and MEDLINE and shows how these two databases, when searched together in SF, complement each other in covering the drug literature. In addition to the extended coverage of the literature, SF provides sophisticated (but easy-to-use) refining and analytical tools not available on some other platforms.